Associations between lower limb injuries and the menstrual cycle phases in football players - Siippainen, Emma (2025)
Siippainen, E. 2025. Associations between lower limb injuries and the menstrual cycle phases in football players. Faculty of Sport and Health Sciences, University of Jyväskylä. Master`s thesis in Exercise Physiology. 63 p.